ANALISIS VEGETASI KAWASAN KARST GOMBONG SELATAN KEBUMEN JAWA TENGAH - Arfiani Salam Suhendar; Edy Yani; Pudji Widodo (Scripta Biologica, 2018)
Karst area is a well-developed porosity landscape with a specific condition as a result of soluble rock development through a process of karstification. The karst soil has low nutrients, but high calcium and magnesium content. Due to its unique environmental characteristics, karst vegetation differs from other areas. This study aimed to determine the community structure and species composition of vegetation in the karst area of Gombong Selatan and to compare the environmental factors affecting the plant of the karst area. This study was conducted in the border of Watukelir and Pakuran Villages. The method was a survey with sampling quadrat sizes used of 10 x 10 m for trees, 5 x 5 m for saplings, and 2 x 2 m for understorey vegetation. The variables observed were plant species and number of trees, saplings, and understorey. The environmental factors measured were air temperature, humidity, soil pH, and soil moisture. Data were analyzed using Importance Value Index (IVI), Shannon-Wienner Diversity Index (H’), Evenness Index (E), and Similarity Index (IS). The results showed there were 22 species of understoreys, five species of saplings, and seven species of trees. The understoreys were found dominated by Axonopus compressus dan Cyperus rotundus, in the other category, Tectona grandis and Albizia chinensis were dominated saplings and trees. Humidity and soil moisture were suggested the important environmental factors for plant diversity in karst area of Gombong Selatan